Phytochemical Profile and Antioxidant Activities of Aqueous Extract of Moringa oleifera (Lam) Collected from DR Congo and Kenya - Valence Bwana Mutwedu; Albert Wafula Nyongesa; Jafred Mulama Kitaa; Jemima Achieng Oduma; James Mucunu Mbaria (Turkish Journal of Agriculture: Food Science and Technology)
Moringa oleifera Lam. is one of the most used plants in traditional medicine because of its high antioxidant properties. The antioxidant value, nonetheless, depends on locality where the plant is grown as well as specific parts on the plant. In this study, a phytochemical and antioxidant activity comparison of M. oleifera leaves, seeds and barks were carried out. Fresh leaves, seeds and barks were collected from 2 to 3 years old M. oleifera trees of Bukavu city of South Kivu province in DRC and Masii village of Machackos County in Kenya. A total of 300g of each dried sample powder was mixed with 700 mL of distilled water. Qualitative and quantitative assessment of alkaloids, saponins, phenols, flavonoids, glycosides, terpenoids and tannins were performed following standard methods while the antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Results indicate that only alkaloids were absent in leaves from Kenya and DRC while phenols, flavonoids and tannins were absent in barks. Glycoside in seeds from DRC had the highest concentration (6.17%) followed by alkaloids in seeds from Kenya (5.56%). There was low concentration of terpenoids and flavonoids in all samples compared to other compounds. The highest extract yield was found in leaves from DR Congo (22.5%) and seeds from Kenya (20%). At the highest concentration (10 µg/mL), leaves from Kenya (88.29±1.12 µg/mL) and DRC (80.17±3.59 µg/mL) had the highest percentage inhibition of reactive oxygen-free radicals but lower than the reference standard (92.63±2.76 µg/mL). Leaves from Kenya (23.59 μg/mL) and DRC (28.67 μg/mL) had the highest IC50 compared to mean values of seeds and barks from the two countries. M. oleifera leaves, especially from Kenya, are recommended as a satisfactory antioxidant but can be substituted with seeds and/or barks in order to alleviate the use of leaves which are overused these days.